Obesity as a Risk Factor for Tendinopathy: A Systematic Review - Francesco Franceschi; Rocco Papalia; Michele Paciotti; Edoardo Franceschetti; Alberto Di Martino; Nicola Maffulli; Vincenzo Denaro (International Journal of Endocrinology)
Purpose. In the last few years, evidence has emerged to support the possible association between increased BMI and susceptibility to some musculoskeletal diseases. We systematically review the literature to clarify whether obesity is a risk factor for the onset of tendinopathy. Methods. We searched PubMed, Cochrane Central, and Embase Biomedical databases using the keywords “obesity,” “overweight,” and “body mass index” linked in different combinations with the terms “tendinopathy,” “tendinitis,” “tendinosis,” “rotator cuff,” “epicondylitis,” “wrist,” “patellar,” “quadriceps,” “Achilles,” “Plantar Fascia,” and “tendon.” Results. Fifteen studies were included. No level I study on this subject was available, and the results provided are ambiguous. However, all the 5 level II studies report the association between obesity measured in terms of BMI and tendon conditions, with OR ranging between 1.9 (95% CI: 1.1–2.2) and 5.6 (1.9–16.6). Conclusions. The best evidence available to date indicates that obesity is a risk factor for tendinopathy. Nevertheless, further studies should be performed to establish the real strength of the association for each type of tendinopathy, especially because the design of the published studies does not allow identifying a precise cause-effect relationship and the specific role of obesity independently of other metabolic conditions.